The hand lines: A glimpse of how we are from corporeality - Palacios Cruz, Víctor (Mercurio Peruano, 2016)
Following the heritage of Merleau-Ponty and his defense of the experience and sensitivity as a principle of philosophy, and considering the relevance of artistic expression for its unique proximity to appearances, this dissertation proposes an observation of hands as a significant place of the corporeal body and the human condition. In particular, it highlights his expressive, playful, utilitarian and cognitive ability, and his relationship with community life, its impact in shaping culture and its risks to the technological innovation of our time.